2012
DOI: 10.1017/s1041610211002523
|View full text |Cite
|
Sign up to set email alerts
|

The development of quality indicators to improve psychosocial care in dementia

Abstract: Our multidisciplinary and multinational strategy resulted in a set of unique QIs that aims exclusively at assessing the quality of psychosocial dementia care. Following implementation, these QIs will assist dementia care professionals to individualize and tailor psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…650 QIs were selected from literature [11, 16, 18, 22, 24–54]. After having assessed these QIs, 554 were excluded because they were not about the organisation of palliative care or because of overlap; the remaining 96 QIs were included in a preliminary set of QIs (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…650 QIs were selected from literature [11, 16, 18, 22, 24–54]. After having assessed these QIs, 554 were excluded because they were not about the organisation of palliative care or because of overlap; the remaining 96 QIs were included in a preliminary set of QIs (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…QIs can help trace potential problems or confirm good quality of care and can be used to guide quality improvement processes [10]. They have been used effectively to assess and improve hospital care, [13] primary care, [14] and dementia care [15, 16]. Several studies have also developed QIs to improve the structures and process needed for the delivery of good quality palliative cancer or dementia care [11, 12, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Important requirements for carrying out care plans are consistent and stable staffing, retaining a familiar environment by minimizing relocations (NICE/SCIE, 2006), and staff education (Canadian Coalition for Seniors ' Mental Health, 2006;Vasse et al, 2008).…”
Section: Care Plansmentioning
confidence: 99%
“…The latest review on nonpharmacological interventions concluded that the feasibility of the investigated interventions is limited because of resource requirements [16]. Recently, a set of 12 quality indicators for psychosocial care in dementia in nursing homes was developed as part of the European Collaboration on Dementia project (EuroCoDe), which was initiated by Alzheimer Europe [17]. The results from the first application draw a different picture than what may was suspected.…”
Section: Introductionmentioning
confidence: 99%